NON-TRADITIONAL APPROACH IN WATERCOLOR TECHNIQUE (Scientific journal of the Fergana State University, 2024)
Through creative activities as well as practical assignments, students try unconventional hands-on experiences with watercolor paints and create creative techniques. Focused on interesting practical activities and effective creativity with a new, meaningful approach to the creative process. With this in mind, below, during practical classes, students have access to a number of actions, as well as advice on some aspects of a new, unconventional creative approach in watercolor technique, on chemical methods related to this topic. To do this consistently, it is important to start writing more plein air studies, and students are required to constantly search Only then will students gain some practical experience and be able to discover and master a new creative technique in the aforementioned watercolor technique As a result, they will gain practical knowledge and skills on the topic. This article provides an analysis of options for solving a problem situation regarding the peculiarities of mastering creative methods in watercolor technique with a new non-traditional approach in the process of creative training of students.